2014
DOI: 10.1515/jbcpp-2014-0057
|View full text |Cite
|
Sign up to set email alerts
|

Geraniol attenuates oxidative stress by Nrf2 activation in diet-induced experimental atherosclerosis

Abstract: Supplementation with GOH appreciably prevented the alterations induced by the AD on all the above parameters. Thus, GOH offers marked protection against AD-induced abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 43 publications
2
13
0
1
Order By: Relevance
“…The obtained results have revealed that the terpene elevated Nrf2 protein translocation from cytoplasm to the nucleus, leading to antioxidant and anti‐inflammatory effects . Another monoterpene, geraniol, was studied due to its demonstrated ability to preserve in hamsters, plasma lipid status, endothelial function and antioxidant status, as well as to inhibit lipid peroxidation . The study concluded that the positive influence of geraniol on changes resulted from it influencing oxidative stress are connected with activating Nrf2 as the main antioxidant transcriptional factor.…”
Section: Antioxidant Activity Of Common Terpenoidsmentioning
confidence: 99%
“…The obtained results have revealed that the terpene elevated Nrf2 protein translocation from cytoplasm to the nucleus, leading to antioxidant and anti‐inflammatory effects . Another monoterpene, geraniol, was studied due to its demonstrated ability to preserve in hamsters, plasma lipid status, endothelial function and antioxidant status, as well as to inhibit lipid peroxidation . The study concluded that the positive influence of geraniol on changes resulted from it influencing oxidative stress are connected with activating Nrf2 as the main antioxidant transcriptional factor.…”
Section: Antioxidant Activity Of Common Terpenoidsmentioning
confidence: 99%
“…Anti-proliferation Apoptosis, DNA damage, and cell cycle arrest In vitro [10] Endometrial carcinoma Anti-migration Antiangiogenesis In vitro and in vivo [15] Liver cancer Anti-proliferation Apoptosis In vitro and in vivo [17][18][19] Lung cancer Anti-proliferation Apoptosis In vitro [21] Pancreatic cancer Anti-proliferation Apoptosis In vitro [26] Prostate cancer Anti-proliferation Cell cycle arrest In vitro [28] Skin cancer Anti-proliferation Apoptosis In vivo [30] 100 mg/kg GE showed that the underlying mechanism consists of alleviating the change in the lipid profile and endothelial function marker, promoting antioxidant enzyme activities and abating alterations in the LPO markers and Nrf2 expression. Histologically, GE negatively affected oxidative stress by increasing the activity of Nrf2 [35]. In the meantime, GE could exert anti-inflammatory and antioxidant effects.…”
Section: Colon Cancermentioning
confidence: 96%
“…In addition, studies also reported a significant development of the disease for other hamster strain, with a range of cholesterol from 0.1-1.0% and the period of dietary intervention as early as two weeks up to 40 weeks (Ahmed 2009;Chen et al 2014;Cherng & Shih 2005;Huang et al 2015;Ioriya et al 2002;Jayachandran et al 2015Jayachandran et al , 2015Kanashiro et al 2007;Krause et al 1992;Lin et al 2013;Lin et al 2012;Mawatari et al 2004;Romain et al 2014;Romain et al 2012;Singh et al 2013;Singh et al 2015;Uehara et al 2002;Vide et al 2015;Zha et al 2009).…”
Section: The Role Of High Fat High Cholesterol (Hfhc) Diet In the Devmentioning
confidence: 98%